Isolation and Characterization of Secondary Metabolites from Halophilic Bacillus Species from Marin drive in Mumbai - Sawale A.A., Kadam T.A. and Mitkare S.S. (Journal of Applied Pharmaceutical Science, 2013)
The present study was focussed on production of novel antibiotics from Halophilic bacterial species in Marin drive Mumbai. Bacillus pumilus were isolated from soil and screened for the production of antibiotics by plate assay and then cultured in shake flask fermentation at 30ºC for further studies. The bioactive secondary metabolites producing bacterial isolates were studied for their ability to tolerate 3% NaCl. Identification of Bacillus pumilus strains was done by using biochemical test as well as 16S r-RNA sequencing method. Identification of antibiotics was done by column chromatography as well as thin layer chromatography. Antibiotics was found to be produced by three are bacterial and one are fungal pathogen strains against E-coli (ATCC#2939), Staphylococcus aureus (ATCC# 96), Pseudomonas aeruginosa (ATCC# 2488) and one are fungal pathogen strains against Candida albicans (ATCC# 227) proved to be resistant to antibiotics produced by Bacillus pumilus. The maximum production of antibiotics from Bacillus pumilus against E-coli, Staphylococcus aureus and Candida albicans. Maximum zones of inhibition were observed after 48 hours of incubation at 30ºC against E-coli, Staphylococcus aureus and Candida albicans. After that structural elucidation was done by using IR, MS and NMR spectroscopy respectively.
Keywords: Halophilic bacteria, Antibiotics, E-coli, S